A literature review: Tsunami disaster mitigation in urban areas - Marasabessy, Firdawaty; Nareswari, Ardhya (International Journal of Disaster Management, 2025)
The 2004 tsunami, which affected 12 countries, including Indonesia, became a key lesson for urban disaster risk management. Mitigation is now a top priority to protect residents and assets, as well as boost capacity. This study identifies tsunami mitigation strategies in urban areas by categorizing them into small, medium, and large/metropolitan cities. A systematic literature review was conducted using Scopus, Web of Science, SpringerLink, and Google Scholar from 2014 to 2024, applying the PRISMA protocol. Fifty-six articles informed mitigation models for different city sizes. Results show strategies differ by city scale: small cities use community and ecosystem approaches, medium-sized cities adopt intermediate technologies and spatial policies, while large cities focus on advanced technologies and systemic planning. Four main themes emerged: spatial planning, community capacity, early warning and evacuation systems, and integration of technology and science. This study provides both conceptual and practical guidance for mitigating urban disaster risk.